Grinding Technique on Synthesis of Calixarene and Its Derivatives - Susy Yunita Prabawati; Afifah Mufidati; Titis Ratna Djuwita; Siti Nur Ngaini (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2020)
The synthesis of p-t-butylcalix[6]arene (PK[6]A) and calixresorcinarene derivative compounds, namely C-para-dimethylamino-phenylcalix[4]resorcinarene (CPDAK[4]R) and C-4-hydroxy-phenylcalix[4]-resorcinarene (CHK[4]R), had been carried out by grinding technique. The grinding technique was done with the absence of solvents so that it minimized the waste. Synthesis occurred through electrophilic substitution reactions with KOH as an alkaline catalyst and p-toluene sulfonic acid as an acid catalyst. The three calixarene products were in the form of crystalline solids with a melting point of more than 300°C, insoluble in water with yields of 62.58; 61.94 and 97.49%, respectively. Product characterization using FTIR analysis showed the vibration of the methylene bridge (-CH2-) at a wavenumber of 1473.62 cm-1 and LC-MS analysis for (PK[6]R) showed that the molecular weight was 974.77 g/mole. While the analysis of (CPDAK[4]R) and (CHK[4]R) with 1H NMR showed the presence of protons from the methine bridge (-CH-) that appear at the chemical shift of 4.950 and 3.078 ppm.